Achieving the Trade‐Off between Selectivity and Activity in Semihydrogenation of Alkynes by Fabrication of (Asymmetrical Pd@Ag Core)@(CeO2 Shell) Nanocatalysts via Autoredox Reaction. Issue 8 (19th December 2016) - Song, Shuyan; Li, Kai; Pan, Jing; Wang, Fan; Li, Junqi; Feng, Jing; Yao, Shuang; Ge, Xin; Wang, Xiao; Zhang, Hongjie
Abstract : (Asymmetrical Pd@Ag core)@(CeO2 shell) nanostructures are successfully fabricated via a clean and facile modified autoredox reaction by the preaddition of Pd seeds in the growth solution. In a subsequent catalytic test, it is found that the as‐obtained bimetallic core@shell nanoparticles exhibit excellent catalytic performance in semihydrogenation of alkynes. The trade‐off between selectivity and activity is well realized.